Interpersonal psychotherapy for mood and behavior dysregulation: Pilot randomized trial. Issue 6 (2nd May 2018) - Miller, Leslie; Hlastala, Stefanie A.; Mufson, Laura; Leibenluft, Ellen; Yenokyan, Gayane; Riddle, Mark
Abstract : Background: Youth with chronic irritability and excessive reactivity, diagnosed as disruptive mood dysregulation disorder (DMDD), have social impairment in multiple settings (i.e., peers, school, and home). This paper presents a pilot randomized trial assessing the feasibility, acceptability, and preliminary efficacy of interpersonal psychotherapy (IPT) for mood and behavior dysregulation (IPT‐MBD), an adapted version of IPT for depressed adolescents. IPT‐MBD focuses on decreasing outbursts and irritability and improving interpersonal interactions. Methods: Nineteen adolescents (aged 12–17) with DMDD or its research precursor, severe mood dysregulation, were randomly assigned to IPT‐MBD ( n = 10) or treatment‐as‐usual (TAU, n = 9) in a 24‐week psychosocial intervention study. Assessments of mood symptoms and overall functioning were conducted by an independent evaluator, blinded to treatment, every 4 weeks. Parent and self‐report irritability measures were collected every 4 weeks. Results: Eighty percent of participants randomized to the IPT‐MBD arm completed the study. Also, participants enrolled in the IPT‐MBD arm attended >80% of therapy sessions. Parents and teens agreed that the frequency and duration of therapy were appropriate and were satisfied with IPT‐MBD treatment. Clinical global impression scales for severity and improvement showed statistically greater improvement in the IPT‐MBD group compared to TAU. Conclusions: In this small pilot randomized trial, IPT‐MBD was feasible and acceptable to parents and teens. There was significantly more improvement in the IPT‐MBD group compared to TAU. IPT‐MBD holds promise as a potentially effective psychosocial intervention for clinically impaired youth with DMDD and warrants further investigation in a larger randomized trial.